2018
DOI: 10.1523/eneuro.0249-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of the Effects of Maternal Immune Activation on Rat Cytokines during Pregnancy and Behavior of the Male Offspring Relevant to Schizophrenia

Abstract: Influenza during pregnancy is associated with the development of psychopathology in the offspring. We sought to determine whether maternal cytokines produced following administration of viral mimetic polyinosinic-polycytidylic acid (polyI:C) to pregnant rats were predictive of behavioral abnormalities in the adult offspring. Timed-pregnant Sprague Dawley rats received a single intravenous injection of 4-mg/kg polyI:C or saline on gestational day (GD)15. Blood was collected 3 h later for serum analysis of cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(101 citation statements)
references
References 122 publications
9
86
4
Order By: Relevance
“…The battery of tasks used in the present study was developed from previous research conducted to assess behavioral effects in the offspring of rats subjected to treatment with polyI:C during pregnancy. As the offspring of polyI:C-treated dams display altered behavior in these tasks (Howland et al, 2012; Zhang et al, 2012; Ballendine et al, 2015; Lins et al, 2018) and have reduced PNNs in mPFC (Paylor et al, 2016), we reasoned it would be valuable to assess behavior in the same tasks following ChABC infusions in young adulthood. In general, behavior of the PEN-treated rats was similar to that previously reported for these tasks (Ballendine et al, 2015; Marks et al, 2016; Lins et al, 2018); thus, we are confident in our testing protocols for these groups of rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The battery of tasks used in the present study was developed from previous research conducted to assess behavioral effects in the offspring of rats subjected to treatment with polyI:C during pregnancy. As the offspring of polyI:C-treated dams display altered behavior in these tasks (Howland et al, 2012; Zhang et al, 2012; Ballendine et al, 2015; Lins et al, 2018) and have reduced PNNs in mPFC (Paylor et al, 2016), we reasoned it would be valuable to assess behavior in the same tasks following ChABC infusions in young adulthood. In general, behavior of the PEN-treated rats was similar to that previously reported for these tasks (Ballendine et al, 2015; Marks et al, 2016; Lins et al, 2018); thus, we are confident in our testing protocols for these groups of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Odd object preference was reported as a percentage of the total time exploring the odd object. Note that 25% is chance performance in this task (Lins et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, using a poly I:C MIA model (Patrich et al, 2016), juvenile male rats showed depression in hippocampal excitatory transmission, an effect that did not appear in poly I:C exposed females until adulthood. Moreover, while male (but not female) exposed poly I:C offspring displayed disrupted startle responses to acoustic stimuli, both sexes showed impairments in sociability, visual discrimination and novel object preferences (Lins et al, 2018;Lins et al, 2019). Reported sex differences are likely due to timing of infection, since male and female brains do not develop at the same pace (Anderson, 2003).…”
Section: Discussionmentioning
confidence: 99%